Mechanism of action, efficacy and adverse events of selected drugs used to treat irritable bowel syndrome (IBS): A Literature Review - Łabuda, Mikołaj; Bogucka, Adrianna; Mentel, Oliwia; Sowińska, Teresa; Szema, Agnieszka; Sikora, Jakub; Słojewska, Aleksandra; Kotkowiak, Agata; Królikowska, Klaudia; Knychalska, Karolina (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Irritable bowel syndrome (IBS) is a prevalent functional gastrointestinal disorder, affecting approximately 11% of the global population, with a higher prevalence in women. It is characterised by recurrent abdominal pain and altered bowel habits, classified into four subtypes according to the Rome IV criteria. Treatment strategies include both non-pharmacological and pharmacological approaches. The aim of this review is to demonstrate the complexity of selected drugs used in IBS, with a particular focus on their mechanism of action, effectiveness, and adverse effects. Brief description of the state of knowledge: Drug treatment for IBS includes various classes of medications that target specific IBS subtypes. Managing patients is complex and requires familiarity with diverse drug types and their mechanisms of action. In patients with IBS with diarrhoea, commonly used medications include antibiotics, opioid receptor modulators, 5-HT3 antagonists, and peripheral opioid receptor agonists. In contrast, constipation treatment primarily involves guanylate cyclase C agonists, osmotic laxatives, prostaglandin derivatives, and prokinetics. Additionally, antispasmodics and antidepressants are also used in IBS treatment. The appropriateness of certain medications remains a subject of debate. The most common side effects of pharmacotherapy affect the gastrointestinal tract, though adverse effects involving other systems may also occur. Conclusion: Pharmacological treatment of IBS should be individualized based on the subtype. Given the variability in drug mechanisms, efficacy, and adverse events, a careful assessment of treatment options is essential to optimize therapeutic outcomes.